Sosialisasi Tentang Pemberian Pijat Pada Bayi Dalam Mendukung Penambahan Berat Badan Bayi Di Puskesmas Anggrek Ciburial Barat Kabupaten Bandung - Ika Rahman; Immanuel Immanuel; Moh Ardiansyah; Yuliana Tania (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
Baby massage is the activity of rubbing and stroking a baby’s body in a manner specifically designed for them. This social service is giving baby massage to infants aged 0-24 months, to determine the effect of baby massage on increasing baby weight. This activity was carried out at Posyandu Anggrek Ciburial Barat located in Bandung Regency. The results of this activity showed an increase in body weight in all babies who were given baby massage, an average of 800 grams in 4 meetings. This shows that infant massage optimizes infant growth and development, including increasing food absorption and providing stimulus to infants which play an important role in infant growth and development, including weight gain.Keywords: Baby, Baby Massage, Weight